Comparative Review of Microfinance Regulatory Framework Issues in Benin, Ghana, and Tanzania - Gallardo, Joselito; Ouattara, Korotoumou; Randhawa, Bikki; Steel, William F. (World Bank, Washington, DC, 2012)
The authors investigate the microfinance regulatory regimes in Benin, Ghana, and Tanzania, with a view to identifying key issues and lessons on how the overall regulatory framework affects integration of microfinance institutions into the financial system. The authors find that recognizing different tiers of both regulated and unregulated institutions in a financial structure facilitates financial deepening and outreach to otherwise underserved groups in urban and rural areas. That environment promotes sustainable microfinance under shared performance standards and encourages regulatory authorities to develop appropriate prudential regulations and staff capacity. Case studies of the three countries raise important issues on promoting microfinance development vis-à-vis regulating them. Laws to regulate activities other than intermediation of public deposits into loans can result in disproportionately restrictive and unmanageable standards, even as dynamic microfinance sectors have emerged without conducive regulatory regimes. The authors use the three countries' regulatory experiences to highlight the importance of differentiating when prudential supervision is warranted and when regulatory oversight suffices, and to identify the agencies to carry out regulation. They address an important issue that has received scant attention, measuring and paying for the costs of regulating microfinance, and the need to build technical capacity of supervisory and regulatory staff.